Self-effectiveness in preventing diarrhea and child care: a transversal study - Emanuella Silva Joventino (Online Brazilian Journal of Nursing, 2013)
Aim: To check the association between the levels of maternal self - effectiveness to prevent child diarrhea and the conditions of health and healthcare provided to the children. Method: This is a trans versal study performed in the municipality of Fortaleza, Brazil, with 448 mothers of children under five years old. The interviews were taken using the Scale of Maternal Self - Effectiveness to Prevent Child Diarrhea. During the analysis, chi - square tests an d Likelihood Ratio were used. Results: A significant association was found between levels of self - effectiveness and the variables: care provided to the child out of the home (p=0.03), only breastfeeding until six months old (p=0.001), previous diarrheic e pisode (p=0.001), the fact that the child has any pathology (p=0.020), hospitalization of the child during the first month of life (p=0.038) and vaccination against rotavirus (p=0.003). Conclusion: Self - effectiveness must be taken seriously during the dev elopment and implementation of interventions, with regards to improve maternal care provided to children.